(untitled) (Research, Society and Development, 2022)
The Fetal Alcohol Spectrum Disorder occurs due to the consumption of alcohol by the mother during the gestational period and constitutes, currently, a serious problem, as it contributes to the appearance of a series of inborn defects in the child, especially with regard to child neurodevelopment. In that way, the objective of this study was to carry out a bibliographic review about this topic, with the goal of analyzing the consequences on the neurodevelopment of the newborn caused by this syndrome. It consists of a qualitative study that made use of twenty-one articles from 2009 to 2021. Under this bias, it was noted that the most affected systems by the fetal alcohol spectrum disorder were the cardiovascular and the nervous system, and the main clinical presentations were heart malformations and modifications in physical and neural development. It was also noticed that despite the evident harm derived from the ingestion of alcohol during pregnancy it remains a critical problem. For this reason, it is necessary to emphasize early diagnosis and intervention, as well as the promotion of research specifically focused on this subject.